2012
DOI: 10.1007/s11357-012-9410-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome sequencing of the aging rat brain reveals dynamic RNA changes in the dark matter of the genome

Abstract: Brain aging frequently underlies cognitive decline and is a major risk factor for neurodegenerative conditions. The exact molecular mechanisms underlying brain aging, however, remain unknown. Whole transcriptome sequencing provides unparalleled depth and sensitivity in gene expression profiling. It also allows non-coding RNA and splice variant detection/comparison across phenotypes. Using RNA-seq to sequence the cerebral cortex transcriptome in 6-, 12- and 28-month-old rats, age-related changes were studied. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 43 publications
(58 reference statements)
7
67
0
1
Order By: Relevance
“…The U-shaped cluster is enriched for cell cycle and DNA replication genes (Table S4), suggesting that the oldest group on average shows lower levels of cellular stress than the animals sampled at median lifespan, possibly because they delayed or escaped age-dependent dysfunctions, as it is the case for human centenarians (Evert et al ., 2003). Inversions in the direction of age-dependent gene expression are prominent in the postnatal primate cortex (Somel et al ., 2010; Colantuoni et al ., 2011) and also observed in the rat brain (Wood et al ., 2013). One of these turning points is observed around the age of 60 years in humans (Colantuoni et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The U-shaped cluster is enriched for cell cycle and DNA replication genes (Table S4), suggesting that the oldest group on average shows lower levels of cellular stress than the animals sampled at median lifespan, possibly because they delayed or escaped age-dependent dysfunctions, as it is the case for human centenarians (Evert et al ., 2003). Inversions in the direction of age-dependent gene expression are prominent in the postnatal primate cortex (Somel et al ., 2010; Colantuoni et al ., 2011) and also observed in the rat brain (Wood et al ., 2013). One of these turning points is observed around the age of 60 years in humans (Colantuoni et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many splicing factors show age‐related changes in their expression that correlate with changes in alternative splicing during aging (Harries et al, 2011; Lee et al, 2016; Mazin et al, 2013; Rodríguez et al, 2016; Tollervey et al, 2011; Wood, Craig, Li, Merry, & Magalhães, 2013). For example, as many as one‐third of all splicing factors exhibit altered expression with age in human blood (Holly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wood et al [52] used RNA-seq to sequence the cerebral cortex transcriptome in 6-, 12-and 28-month-old rats, and revealed that protein coding genes related to MHC II presentation and serotonin biosynthesis were differentially expressed in aging. Dillman et al [53] reported a high-resolution transcriptome dataset of mouse cerebral cortex at embryonic and adult stages using RNA-Seq and found many differences in gene expression, splicing, and RNA editing between embryonic and adult cerebral cortex, such as cell cycle, DNA damage response and repair in embryonic brain and immune response in adult brain.…”
Section: Evidence For Molecular Inflammation In the Aging Process As mentioning
confidence: 99%